2007
DOI: 10.1080/13880200701501342
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory, Antinociceptive, and Neuropharmacological Activities ofClerodendron viscosum.

Abstract: The crude methanol extract of Clerodendron viscosum Vent. (Verbenaceae) leaves was evaluated for its antiinflammatory, antinociceptive, and neuropharmacological activities. When given orally to rats at doses of 200 and 400 mg=kg of body weight, the extract showed a significant (p < 0.001) anti-inflammatory activity against carrageenan-induced rat paw edema comparable with the standard drug phenylbutazone at the dose of 100 mg=kg of body weight. It also produced a significant writhing inhibition in acetic acid-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 13 publications
2
11
0
Order By: Relevance
“…In addition, writhing response is widely accepted as a model visceral pain due to the release of endogen mediators of pain, such as prostaglandins, kinins, etc. (Derardt et al, 1980;Ahmed et al, 2007;Sulaiman et al, 2008;Zheng et al, 2009). Based on findings obtained in the present study, it was concluded that CME possesses a significant antinociceptive activity both at spinal and supraspinal levels.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…In addition, writhing response is widely accepted as a model visceral pain due to the release of endogen mediators of pain, such as prostaglandins, kinins, etc. (Derardt et al, 1980;Ahmed et al, 2007;Sulaiman et al, 2008;Zheng et al, 2009). Based on findings obtained in the present study, it was concluded that CME possesses a significant antinociceptive activity both at spinal and supraspinal levels.…”
Section: Discussionsupporting
confidence: 69%
“…CME was tested for the presence of alkaloids, tannins, reducing sugar, and flavonoids by using standard phytochemical procedures. In each test we used 10% (w/v) methanol solution of extract (Trease & Evans, 2002;Ahmed et al, 2007).…”
Section: Phytochemical Screeningmentioning
confidence: 99%
“…In each test, we used 10% (w/v) methanol solution of extract was used (Evans, 2002;Ahmed et al, 2007). The total phenolic content of extracts was determined using to the Folin-Ciocalteu method (Akkol et al, 2008).…”
Section: Phytochemical Screeningmentioning
confidence: 99%
“…Previous phytochemical investigation of the plant revealed the presence of alkyl sterols and 2,-(3,4-dehydroxyphenyl) ethanol 1-O-α-2 rhamnopyranosyl-(1→3)-β-D-(4-O-caffeoyl) glycopyranoside or acteoside 6,7. Previous work has reported hepatoprotective, anti-inflammatory, antinociceptive, and neuropharmacological activities of C. infortunatum 8–10. Until now, there have been no reports on antidiabetic investigations of this plant.…”
Section: Introductionmentioning
confidence: 99%